Peningkatan Kemampuan Motorik Kasar Anak Usia Dini Melalui Pembelajaran Gerak Tari Ayam - Indrawati, Triana; Rahmah, Nabila Aulia (Universitas Islam Negeri Raden Intan Lampung, 2020)
Chicken Dance Motion is a dance movement with the imagination like being a Chicken who is looking for food, walking, jogging, and so forth. Motion as the main ingredient in dance, is used as a medium to express ideas of what they think and feel. Chicken dance movements can improve the gross motor development of children. Motor Development means the development of controlling physical movements through coordinated nerve center, nerve and muscle activities. This study aims to describe the pre-cycle conditions of chicken dance learning in B1 group children and explain whether the method of chicken dance learning can improve the gross motor development of early childhood. This type of research is a classroom action research conducted collaboratively between researchers and teachers. The study was conducted in two cycles. The research subjects were children of group B1 TKIT Mutiara Hati Petarukan Pemalang. The results showed that there was an increase in children's gross motor development through chicken dance movements in the B1 group TKIT Mutiara Hati Petarukan Pemalang.